Papel de SOCS2 e NLRP3 na encefalomielite autoimune experimental - Bruno Cabral de Lima Oliveira (2015)
Experimental Autoimmune Encephalomyelitis (EAE) is the most widely used animal model for the study of Multiple Sclerosis, an inflammatory disease of the central nervous system (CNS). Suppressor of Cytokine Signaling (SOCS) family proteins play a critical role in regulating cytokine responses. SOCS2 is known to be a crucial modulator of physiological responses and in the pathogenesis of certain allergy and infectious diseases. The role of SOCS2 during EAE has not been explored yet. EAE was induced in WT and SOCS2 deficient (-/-) mice using Myelin Oligodendrocyte Glycoprotein peptide (MOG35-55). Brain and spinal cord samples were examined during the peak (day 14) and recovery phase (day 28) of the disease. SOCS2 is upregulated in brain of WT mice after EAE induction and SOCS2-/- mice were more resistant to acute phase development. The postponement of the first severe signs of the disease in SOCS2-/- mice was associated with decreased expression of 5-LO, AhR and IRF1 in the brain and reduced frequency of inflammatory T cells (IFN-+ and IL-17+) and modulation of cytokines in the brain and spinal cord. However, while in WT mice maximal clinical EAE score was followed by a progressive recovery, the SOCS2-/- mice were unable to recover from the locomotor damage that occurred during the acute phase, which was associated with greater inflammation in the CNS, resulting in a prolonged inflammatory response in the late phase of EAE. We also demonstrate that NLRP3 activity specifically in the CNS is an amplifier factor of EAE. NLRP3 is expressed and functional in microglia, but not in astrocytes. Furthermore, F4/80+ cells from peripheral organs from animals with EAE are able to activate microglia NLRP3 in vitro, but do not in astrocytes. It was also shown that microglia produce more efficiently IL-1 after co-culture with lymphocytes Th17 in the presence of MOG. Altogether, these results suggest that SOCS2 plays a dual role in the immune response during EAE. It is necessary for induction of the acute phase but plays a crucial beneficial role in the recovery stage of the disease by controlling the regulatory component of EAE. In addition, NLRP3 specific activity in the CNS is an important factor for severity of disease.